2016
DOI: 10.1007/s11239-016-1459-8
|View full text |Cite
|
Sign up to set email alerts
|

Prethrombotic, prothrombotic, thrombophilic states, hypercoagulable state, thrombophilia etc.: semantics should be respected even in medical papers

Abstract: The study of prothrombotic or thrombophilic states have drawn considerable attention during the past two decades. This was the result of the increasing number of thrombotic events, both arterial and venous reported all over the world but especially in the developed countries. This wealth of studies and papers have not always respected the semantical significance of the various terms used, namely prethrombotic state, hypercoagulable state, thrombophilic or prothrombotic state, thrombophilia, susceptibility to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The prethrombotic state, also known as the hypercoagulable state, refers to a pathological state characterized by an imbalance between the anticoagulant system and the coagulation system, which makes thrombus formation possible. FIB, FDP, and D-D levels are reliable indicators of the prethrombotic state, and D-D levels are also used to reflect secondary fibrinolysis 33 . Our results also showed that the sequential application of TXA during the perioperative period can better stabilize the structure of FIB and reduce the generation of FDP and D-D.…”
Section: Discussionmentioning
confidence: 99%
“…The prethrombotic state, also known as the hypercoagulable state, refers to a pathological state characterized by an imbalance between the anticoagulant system and the coagulation system, which makes thrombus formation possible. FIB, FDP, and D-D levels are reliable indicators of the prethrombotic state, and D-D levels are also used to reflect secondary fibrinolysis 33 . Our results also showed that the sequential application of TXA during the perioperative period can better stabilize the structure of FIB and reduce the generation of FDP and D-D.…”
Section: Discussionmentioning
confidence: 99%
“…We also found the trend of HCT changes in the TXA group were relatively small, which is consistent with the research results of Dong W et al and Kelly M et al 45 , 46 D-D can be a reliable indicator of the pre-thrombotic state. 47 Interestingly, the average level of D-D at postoperative day 1 in TXA group is significantly lower than that in control group [2815 (1717.5–4497.5) ug/L VS 6415 (3917.5–8482.5) ug/L, P < 0.001)]. This indicates that TXA can effectively reduce postoperative D-D levels, which is supported by Dong et al 46 In addition, neither group of patients experienced any postoperative adverse events or TXA related complications.…”
Section: Disscussionmentioning
confidence: 99%
“…Namely, the pathological conditions favoring thrombosis caused by functional changes in vascular endothelial cells, platelets, coagulation, anticoagulation and fibrinolysis systems ( 3 ). It’s been reported that the pre-thrombotic state is highly associated with the occurrence of VTE, whereas the pre-thrombotic state is attributed to several risk factors, such as malignant tumor and fracture ( 4 , 5 ). Therefore, the early identification of patients with potential risk of pre-thrombotic state are essential to the progress of VTE.…”
Section: Introductionmentioning
confidence: 99%